Characterization and sequence of a Thermomonospora fusca xylanase. - Irwin, D (1994)
TfxA is a thermostable xylanase produced by the thermophilic soil bacterium Thermomonospora fusca. The enzyme was purified to homogeneity from the culture supernatant of Streptomyces lividans transformed by plasmid pGG92, which carries the gene for TfxA, xynA. The molecular mass of TfxA by sodium dodecyl sulfate-polyacrylamide gel electrophoresis is 32 kDa. TfxA is extremely stable, retaining 96% of its activity after 18 h at 75 degrees C. It has a broad pH optimum around pH 7 and retains 80% of its maximum activity between pH 5 and 9. The native enzyme binds strongly to both cellulose and insoluble xylan even though it has no activity on cellulose. Treatment of TfxA with a T. fusca protease produced a 24-kDa catalytically active fragment that had the same N-terminal sequence as TfxA. The fragment does not bind to cellulose and binds weakly to xylan. The Vmax values for TfxA and the fragment are 600 and 540 mumol/min/mg, respectively, while the Kms are 1.1 and 2.3 mg of xylan per ml, respectively. The DNA sequence of the xynA gene was determined, and it contains an open reading frame that codes for a 42-amino-acid (42-aa) actinomycete signal peptide followed by the 32-kDa mature protein. There is a 21-aa Gly-Pro-rich region that separates the catalytic domain from an 86-aa C-terminal binding domain. The amino acid sequence of the catalytic domain of TfxA has from 40 to 72% identity with the sequence of 12 other xylanases from seven different organisms and belongs to family G.(ABSTRACT TRUNCATED AT 250 WORDS)